2020
DOI: 10.1039/d0em00238k
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol tracers and related polar organic compounds between urban and rural areas in the Eastern Mediterranean region: source apportionment and the influence of atmospheric oxidants

Abstract: Fine particle samples were collected during summer at an urban (LIM) and a rural/background (AGM) site of Cyprus. They were analyzed for pinene and isoprene secondary organic aerosol (PSOA-ISOA) tracers,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(24 citation statements)
references
References 142 publications
(176 reference statements)
0
24
0
Order By: Relevance
“…Among the 10 compounds with the highest intensities (≥3 × 10 8 ), four were identified at Level 4, two were identified at Level 2, while four were identified at Level 1 through the comparison with reference standards (Table 2). Those identified at Level 1 were typical dicarboxylic acids, such as 38 which was also found in the sample. We also identified levulinic acid (C 5 H 8 O 3 ), which is a γ-ketoacid.…”
Section: Methods Performances and Application On Realmentioning
confidence: 99%
“…Among the 10 compounds with the highest intensities (≥3 × 10 8 ), four were identified at Level 4, two were identified at Level 2, while four were identified at Level 1 through the comparison with reference standards (Table 2). Those identified at Level 1 were typical dicarboxylic acids, such as 38 which was also found in the sample. We also identified levulinic acid (C 5 H 8 O 3 ), which is a γ-ketoacid.…”
Section: Methods Performances and Application On Realmentioning
confidence: 99%
“…The first-generation products have been found to form under atmospheric conditions with OH or ozone and at lower NO x concentrations, while an increase in NO x concentrations has yielded more higher-generation products. 34,44 In smog chamber experiments by Müller et al , 44 cis -pinonic acid was demonstrated to react with OH radicals, as pinic acid was not observed to produce 3-MTBCA. Occurring in the gas phase, cis -pinonic acid was observed to have higher volatility, and its fraction increased at higher chamber temperatures leading to higher 3-MBTCA concentrations.…”
Section: Oxidized Compounds In the Atmospherementioning
confidence: 99%
“…13,33 Ozonolysis also contributes to isoprene oxidation in which typical products are formed, albeit less compared to the OH-initiated reactions. 34…”
Section: Oxidized Compounds In the Atmospherementioning
confidence: 99%
See 2 more Smart Citations